RESOLUSI KONFLIK PEMANFAATAN TANAH ULAYAT Nagari Lubuk Kilangan Vs PT Semen Padang - , Septa Dolesri; , Drs. Haryanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis discusses the customary land (tanah ulayat) conflicts between Nagari Lubuk Kilangan with PT Semen Padang. Customary land conflicts in Nagari Lubuk Kilangan Padang was triggered by the publication of the Governor of West Sumatera Exploitation SIPD the 412.03 ha area on June 6, 1997, which is the area belong to Lubuk Kilangan villages. The problem is, the local government issue permits without communicate with KAN Lubuk Kilangan as authorities of customary land. West Sumatra Governor also ignore Regional Office of Forestry letter stating that part of the land 412.03 ha is forest area. This study uses case study approach because the cases of conflict in the present context and the escalation of the conflict remain unresolved until today. The researcher systematically try to dig information about conflicts of customary land to find out how the anatomy of conflict and conflict resolution that has been done. Data were collected by in-depth interviews, documentary studies, and observation techniques. Based on the results of the study, showed that the customary land conflicts involving religious actors with different interests and positions. Conflict that lasted so long is due to a variety of factors ranging of political and policy factors, identity of the villages which are threatened, economic factors, and environmental factors. The root of this conflict is their customary land use that is not in accordance withMinangkabau traditional law. A high conflict dynamics and complexity of actors makes the issue of conflict has shifted from issues of identity into economic issues. Agreement PT SP and KAN Lubuk Kilangan to end the conflict is achieved by payment crop compensation in 2001 and the agreement on the payment of wages in 2004. The compensation of settelement was as much at 3 stages. However, the conflict resolution efforts are being hampered because BPN Padang letter explaining that most of the area is 412.03 ha of forest land.